Multifunctional polyketide synthase genes identified by genomic survey of the symbiotic dinoflagellate, Symbiodinium minutum. (December 2015) - Beedessee, Girish; Hisata, Kanako; Roy, Michael; Satoh, Noriyuki; Shoguchi, Eiichi
Abstract Background Dinoflagellates are unicellular marine and freshwater eukaryotes. They possess large nuclear genomes (1.5–245 gigabases) and produce structurally unique and biologically active polyketide secondary metabolites. Although polyketide biosynthesis is well studied in terrestrial and freshwater organisms, only recently have dinoflagellate polyketides been investigated. Transcriptomic analyses have characterized dinoflagellate polyketide synthase genes having single domains. The GenusSymbiodinium, with a comparatively small genome, is a group of major coral symbionts, and theS. minutum nuclear genome has been decoded. Results The present survey investigated the assembledS. minutum genome and identified 25 candidate polyketide synthase (PKS) genes that encode proteins with mono- and multifunctional domains. Predicted proteins retain functionally important amino acids in the catalytic ketosynthase (KS) domain. Molecular phylogenetic analyses of KS domains form a clade in whichS. minutum domains cluster within the protist Type I PKS clade with those of other dinoflagellates and other eukaryotes. Single-domain PKS genes are likely expanded in dinoflagellate lineage. Two PKS genes of bacterial origin are found in theS. minutum genome. Interestingly, the largest enzyme is likely expressed as a hybrid non-ribosomal peptide synthetase-polyketide synthase (NRPS-PKS) assembly of 10, 601 amino acids, containing NRPS and PKS modules and a thioesterase (TE) domain. We also found intron-rich genes with the minimal set of catalytic domains needed to produce polyketides. Ketosynthase (KS), acyltransferase (AT), and acyl carrier protein (ACP) along with other optional domains are present. Mapping of transcripts to the genome with the dinoflagellate-specific spliced leader sequence, supports expression of multifunctional PKS genes. Metabolite profiling of culturedS. minutum confirmed production of zooxanthellamide D, a polyhydroxy amide polyketide and other unknown polyketide secondary metabolites. Conclusion This genomic survey demonstrates thatS. minutum contains genes with the minimal set of catalytic domains needed to produce polyketides and provides evidence of the modular nature of Type I PKS, unlike monofunctional Type I PKS from other dinoflagellates. In addition, our study suggests that diversification of dinoflagellate PKS genes comprises dinoflagellate-specific PKS genes with single domains, multifunctional PKS genes with KS domains orthologous to those of other protists, and PKS genes of bacterial origin.